The Impact Of Parents' Jobs On Children's Psychology In Lembah Bahbutong Village 1 - Febri Adhari Syahwitri; Junita Hanum Eka Putri; Mutia Adella; Nefi Darmayanti; Nakita Augydia Lesmana (Jurnal Multidisiplin Sahombu, 2024)
The role of parents in development children are very important , including in matter development emotional and psychological . Research This aiming For know influence parents ' job to development psychological children in Lembah Bahbutong Village I. Research This use method study field . Research results This show that There is influence parents ' job to development psychological children that occurred in Lembah Bahbutong I Village, namely There is impact positive and impact negative , impact positive that is increase discipline and responsibility answer child Study value Work hard and disciplined from working parents , developing​​ independence child , Improve awareness will importance Education and Development ability social . While impact the negative is lack of attention and time , Children feel not enough get attention and time from busy parents​​ work . Next stress and anxiety , experiencing difficulty in learning and developing behavior negative , such as aggressiveness , withdrawal yourself , or habit bad other .